Acute and subacute toxicity study of the ethanol extract from Lonicera japonica Thunb. - S. Thanabhorn (2018)
The ethanol extract from the leaves of Lonicera japonica Thunb. was evaluated for acute and subacute toxicity. The single oral dose of the ethanol extract at 5000 mg/kg did not produce mortality or significant changes in the general behaviour and gross appearance of the internal organs of rats. In subacute toxicity study, the ethanol extract was administered orally at a dose of 1000 mg/kg/day for a period of 14 days. The satellite group was treated with the ethanol extract at the same dose and the same period and kept for another 14 days after treatment. There were no significant differences in the body and organ weights between the control and the treated group of both sexes. Hematological analysis and clinical blood chemistry revealed no toxicity effects of the extract. Pathologically, neither gross abnormalities nor histopathological changes were observed. © 2006 Elsevier Ireland Ltd. All rights reserved.